Assessment of climate change impacts on rainfall series in Peninsular Malaysia using statistical methods - Lee, Amanda Sean Peik (2017)
There is growing interest in quantifying the impact of climate change on extreme hydrologic events where failing to integrate the effect of climate change in rainfall estimation will underestimate the severity of the events and the adequacy of current hydraulic structure designs. The purpose of this study aims is to assess the rainfall trend and frequency analysis with impact from climate change in Peninsular Malaysia using statistical methods.